Neurophysiological markers of asymmetric emotional contagion: implications for organizational contexts - Boukarras, Sarah; Ferri, Donato; Borgogni, Laura; Aglioti, Salvatore Maria (Frontiers in Integrative Neuroscience, 2024)
Emotions play a vital role within organizations, impacting various crucial aspects of work such as job satisfaction, performance, and employee well-being. Understanding how emotional states spread in organizational settings is therefore essential. Recent studies have highlighted that a leader’s emotional state can influence their followers, with significant consequences on job performance. Leaders thus possess the ability to influence their employees’ psychological state and, consequently, their well-being. However, the biological underpinnings of emotional contagion from leaders to followers remain unexplored. The field of interpersonal (neuro)physiology, which involves recording brain and peripheral activity of multiple individuals during interactions, holds great potential for investigating this phenomenon. Analyzing the time-lagged synchronization of neurophysiological activity during interactions may serve as a measure of the leader’s influence on their followers in organizational contexts. In this “mini review,” we examine empirical studies that have employed interpersonal (neuro)physiology to quantify the asymmetrical contagion of emotions in different contexts. Asymmetrical contagion was operationalized as the unidirectional influence exerted by one individual (i.e., the “sender”) to another one (i.e., the “receiver”), whereby the receiver’s state can be predicted by the sender’s one. The reviewed literature reveals that delayed synchronization of physiological states is a widespread phenomenon that may underpin the transmission of emotions. These findings have significant implications for various aspects of organizational life, including leader-to-employee communication, and could drive the development of effective leadership training programs. We propose that Organizational Neuroscience may benefit from including interpersonal neurophysiology in its methodological toolkit for laboratory and field studies of leader-follower dynamics.